2013
DOI: 10.1038/npp.2013.343
|View full text |Cite
|
Sign up to set email alerts
|

12-Week, Placebo-Controlled Trial of Add-on Riluzole in the Treatment of Childhood-Onset Obsessive–Compulsive Disorder

Abstract: Many children with childhood-onset obsessive-compulsive disorder (OCD) fail to respond adequately to standard therapies. Evidence from preclinical and clinical studies suggests that the glutamatergic neurotransmitter system might be an alternative treatment target. This study examined the efficacy of riluzole, a glutamatergic modulator, as an adjunctive therapy for children with treatment-resistant OCD. In a 12-week, double-blind, placebo-controlled study, 60 treatment-resistant children and adolescents (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 31 publications
0
44
0
2
Order By: Relevance
“…Although uncontrolled studies had previously shown effects in children [101] and adults [102,103], the first RCT trial conducted among (S)SRI non-responders did not show any effect over pill placebo. However, 28 % of participants had concomitant autism disorder [104].…”
Section: Medicationsmentioning
confidence: 98%
“…Although uncontrolled studies had previously shown effects in children [101] and adults [102,103], the first RCT trial conducted among (S)SRI non-responders did not show any effect over pill placebo. However, 28 % of participants had concomitant autism disorder [104].…”
Section: Medicationsmentioning
confidence: 98%
“…Riluzole has shown some positive clinical responses in refractory OCD patients [114] . However, in more controlled studies, results have shown only minimal benefits [115,116] .…”
Section: Glutamatementioning
confidence: 99%
“…Por último, algunas investigaciones abiertas sugirieron que el riluzol, un modulador del glutamato, podría mejorar el TOC resistente en pacientes adultos (58) y menores de edad (59); sin embargo, los resultados de posteriores estudios controlados con placebo son dudosos en adultos (60) y negativos en niños (61 Rev Neuropsiquiatr 79 (4), 2016.…”
Section: Fármacos Relacionados a La Función Glutamatérgicaunclassified